(untitled) (Journal of Economic Research & Business Administration, 2019)
This review article presents materials collected during the preparation of the National Science Report 2018. Its goal is to analyze the main trends in the development of economic science in Kazakhstan, identify positive and negative factors affecting its development, and suggestion recommendations for further development. Through the scientific analysis based on the publications of the last three years, the statistical data of the information resources such as Web of Science of the company Clarivate Analytics and Scopus of the company Elsevier present the main directions of development of Kazakhstan’s economic science and its place in world science; the analysis of the situation in the field of economic research. The most significant results of economic research in Kazakhstan, indicators of research activity of scientists (number of publications, citation index, impact factor of journals) are indicated. Attention is drawn to the achievements of Kazakhstan science as a result of cooperation with foreign scientists and scientific organizations. The evaluation of the strengths and weaknesses of Kazakhstan’s research in the field of economics based on the index of scientific specialization in the categories of Web of Science Core Collection was made, and data on the preparation of PhD in economics were presented. Formulated proposals for promising areas of economic science and the organization of scientific research in the field of economics.